2019
DOI: 10.18383/j.tom.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

Defining Characteristics of Nodal Disease on PET/CT Scans in Patients With HIV-Positive and -Negative Locally Advanced Cervical Cancer in South Africa

Abstract: Literature reports increased FDG nodal uptake in HIV-positive patients. Our aim is to identify differences in presentation and characteristics of FDG-avid lymph nodes between HIV-positive and HIV-negative locally advanced cervical cancer (LACC) patients in our clinical setting. We evaluated 250 pre-treatment 18F-FDG PET/CT imaging studies from women screened for a phase III randomised controlled trial investigating modulated electro-hyperthermia as a radiosensitiser (Ethics approval: M120477). The number of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Minnaar et al evaluated 250 pre-treatment PET-CT scans for patients with cervical cancer enrolling in a phase III trial; 128 of the participants were people living with HIV, of whom 82% were on antiretroviral therapy. The pattern of presentation and nodal characteristics did not differ based on HIV status; however, nodal biopsies were not performed or evaluated in this study 23…”
Section: Cervical Malignancy In People Living With Hivmentioning
confidence: 98%
See 1 more Smart Citation
“…Minnaar et al evaluated 250 pre-treatment PET-CT scans for patients with cervical cancer enrolling in a phase III trial; 128 of the participants were people living with HIV, of whom 82% were on antiretroviral therapy. The pattern of presentation and nodal characteristics did not differ based on HIV status; however, nodal biopsies were not performed or evaluated in this study 23…”
Section: Cervical Malignancy In People Living With Hivmentioning
confidence: 98%
“…The pattern of presentation and nodal characteristics did not differ based on HIV status; however, nodal biopsies were not performed or evaluated in this study. 23 Treatment Disparities Suneja et al conducted a National Cancer Database analysis of 10 265 people living with HIV and 2 219 232 HIV-uninfected patients between 2003 and 2011 in the USA, which found that people living with HIV were less likely to receive cancer treatment compared with HIV-uninfected patients, even after adjusting for clinical and sociodemographic variables. For cervical cancer, people living with HIV were nearly three times as likely to be untreated for cancer (adjusted OR 2.81, 95% CI 1.77 to 4.45) compared with HIVuninfected controls.…”
Section: Diagnosismentioning
confidence: 99%
“…The cervix cancers were studied in a Phase III double-arm randomized prospective controlled trial involving two–two groups in both arms, patients ±HIV [ 67 , 68 ]. Metabolic response (MR) was measured by PET [ 69 ]. The advantages of mEHT appeared in the higher complete metabolic response (CMR) of the HIV groups compared to the control groups.…”
Section: Clinical Validationmentioning
confidence: 99%